Tumor immune microenvironment alterations using induction cetuximab in a phase II trial of deintensified therapy for p16‐positive oropharynx cancer. Issue 5 (18th March 2023) - Smith, Joshua D.; Ludwig, Megan L.; Bhangale, Apurva D.; Brummel, Collin; Swiecicki, Paul L.; Worden, Francis P.; Chinn, Steven B.; Stucken, Chaz L.; Rosko, Andrew J.; Prince, Mark E. P.; Malloy, Kelly M.; Casper, Keith A.; et al.
Abstract: Background: We sought to characterize early changes in CD8 + tumor‐infiltrating lymphocytes and tumor transcriptomes after induction cetuximab in a cohort with p16‐positive oropharyngeal cancer on a phase II clinical de‐escalation trial. Methods: Tumor biopsies were obtained before and 1 week after a single cetuximab loading dose in eight patients enrolled in a phase II trial of cetuximab and radiotherapy. Changes in CD8 + tumor‐infiltrating lymphocytes and transcriptomes were assessed. Results: One week after cetuximab, five patients (62.5%) had an increase in CD8 + cell infiltration with a median (range) fold change of +5.8 (2.5–15.8). Three (37.5%) had unchanged CD8 + cells (median [range] fold change of −0.85 [0.8–1.1]). In two patients with evaluable RNA, cetuximab induced rapid tumor transcriptome changes in cellular type 1 interferon signaling and keratinization pathways. Conclusions: Within 1 week, cetuximab induced measurable changes in pro‐cytotoxic T‐cell signaling and immune content.